Preoperative Serum IL6, IL8, and TNF-α May Predict the Recurrence of Hepatocellular Cancer - Huayong Cai; Yu Zhang; Fanyu Meng; Chao Cui; Hao Li; Minghao Sui; Haoyun Zhang; Shichun Lu (Gastroenterology Research and Practice)
Purpose. As we all know, curative resection remains the only effective treatment for hepatocellular cancer (HCC). However, systemic inflammatory response syndrome always correlates with surgery, which may impose an impact on the clinical outcome of HCC patients who had undergone curative treatment. The present study is aimed at exploring the correlation between perioperative inflammatory mediators and recurrence risk of HCC. Methods. This study retrospectively included 157 histologically confirmed single HCC patients (88 patients developed HCC again) who had received radical hepatectomy between January 2016 and May 2018 at the Department of Hepatobiliary Surgery, the People’s Liberation Army General Hospital (PLAGH), China. The cut-off values for predicting recurrence were determined by receiver operating characteristic (ROC) curve analysis with estimation of the Youden index. Recurrence-free survival (RFS) was assessed using the Kaplan-Meier method, and the difference was compared between groups by the log-rank test. Univariate/multivariate analysis was performed to identify independent risk factors of postoperative tumor recurrence. Results. The perioperative serum IL1, IL2, and IL10 levels showed no difference between groups, whereas the serum IL6, IL8, and TNF-α levels showed significant differences between groups. High preoperative serum IL6, IL8, and TNF-α levels were significantly associated with shorter RFS. Multivariate analysis revealed that preoperative serum IL6>8.45 pg/ml, preoperative serum IL8>68 pg/ml, preoperative serum TNF−α>14.9 pg/ml, microvascular invasion (MVI), and maximum tumor size>6 cm were independent predictors of RFS. Conclusions. The present study confirmed that high preoperative serum IL6, IL8, and TNF-α levels were distinctly correlated with the postoperative tumor recurrence risk of HCC patients.